Disclosure of Public Information in Health Services - Muhamad Sarjan; Hayat; Septina Dwi Rahmawati (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
With the presence of Law No. 14/2008 on Public Information Disclosure, this law has provided a legal basis for everyone's right to obtain public information, because every public agency has an obligation to provide and serve requests for public information in a fast, timely, low-cost and simple method. Puskesmas Sape still has patients or the public who are confused about services at Puskesmas Sape due to the ignorance of patients or the public about the procedures and flow of services at Puskesmas Sape. The factor that is the ignorance of the community is due to information that has not been conveyed directly to patients or the community and the lack of information dissemination so that the community still does not fully know the flow and procedure of services at the Sape Health Center. Because public service is one of the government's efforts to fulfill the rights of every citizen, if public services are not fully fulfilled by public organizers, public services can be said to have failed. This study aims to determine how public information disclosure in providing health services at the Sape Health Center and the supporting and inhibiting factors of public information disclosure in health services at the Sape Health Center. The method that researchers use is a descriptive method with a qualitative approach. The implication of the research shows that the implementation of openness in the provision of health services at the Sape Health Center.